THE NAME OF PACIOLI. - Taylor, R. Emmett (The Accounting Review, 1944)
Abstract In a recent issue of the journal The Accounting Review there is an article entitled "The Name of Paciolo" which treats largely of the book "No Royal Road," and especially of the spelling of the name Luca Pacioli, an Italian mathematician. It appears that the accounting material for the article was furnished by one man who is an accountant, and that it was written by another man who is a linguist. A week or so before the appearance of the article, the author had a letter from a gentleman in the accounting field asking him why he used the spelling "Pacioli" rather than "Paciolo." One of the many names which was used for Pacioli was Luca de Pacioli, which means "Luca of the Pacioli family." The "de" has been dropped in many Italian family names and the ending has not been changed. The Catholic Encyclopedia uses this ending, the Encyclopedia Italiana uses this ending and the Encyclopedia Britannica uses this ending. Most of the authors whom the author considers leading authorities in their respective fields used the spelling "Pacioli."